Sarcopenia Coexisting with High Adiposity Exacerbates Insulin Resistance and Dyslipidemia in Saudi Adult Men - Habib SS; Alkahtani S; Alhussain M; Aljuhani O (Diabetes, Metabolic Syndrome and Obesity, 2020)
Syed Shahid Habib,1 Shaea Alkahtani,2 Maha Alhussain,3 Osama Aljuhani4 1Department of Physiology, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 2Department of Exercise Physiology, College of Sport Sciences and Physical Activity, King Saud University, Riyadh, Saudi Arabia; 3Department of Nutrition and Food Sciences, College of Agricultural and Food Sciences, King Saud University, Riyadh, Saudi Arabia; 4Department of Physical Education, College of Sport Sciences and Physical Activity, King Saud University, Riyadh, Saudi ArabiaCorrespondence: Syed Shahid HabibDepartment of Physiology, College of Medicine, King Saud University, PO Box 2925, King Saud University Medical City, Riyadh 11461, Kingdom of Saudi ArabiaTel +966 1-4671616Fax +966 1-4672567Email shahidhabib44@hotmail.comObjective: The associations between sarcopenia, adiposity indices and metabolic dysregulation still remain controversial. We aimed to assess and compare insulin resistance and metabolic profile in sarcopenic and non-sarcopenic obese Saudi adult men.Methods: This cross sectional study was conducted at the College of Sports Sciences, King Saud University, Riyadh. We recruited 312 Saudi adult male individuals and 288 were finally selected for the study. Body composition analysis and hand grip strength (HGS) were estimated by bioimpedance analysis (BIA) and dynamometer in all subjects, respectively. Fasting blood samples were collected for glucose (FBG), basal insulin (BI) and lipid profile. The subjects were divided into three groups based on the body composition parameters, appendicular lean mass (ALM) and body fat percentage (BF%), into non-obese (NonOb) [Normal ALM+< 25 BF%], obese without sarcopenia (ObNonS) [Normal ALM+> 25 BF%] and obese with sarcopenia (ObS) [Low ALM+> 25 BF%].Results: Obese subjects had significantly higher BI, HOMA-IR and HOMA-β compared to non-obese. Moreover, comparison between two obese groups revealed that both BI and HOMA-IR levels were higher in ObS subjects compared to ObNonS individuals revealing that sarcopenia exacerbates the insulin resistance profile. There was a significant trend of higher resistance and lower sensitivity from non-obese to obesity with sarcopenia. Total cholesterol (TC) and triglycerides (TG) were significantly higher and high density lipoprotein cholesterol (HDL-C) was significantly lower in sarcopenic obese subjects compared to non-sarcopenic obese individuals. The worsening effects were more significant at cutoff point of 7.46 on insulin indices and lipid profile showing that sarcopenia associated with obesity exacerbates the dyslipidemia.Conclusion: Our study shows that obesity associated with sarcopenia exhibits significantly greater insulin resistance and dyslipidemia than sarcopenia or obesity per se. Therefore, sarcopenic obesity might be an independent risk factor for metabolic disease progression.Keywords: obesity, sarcopenia, sarcopenic obesity, HOMA-IR, HOMA-β cholesterol, triglycerides (TG), body fat percentage (BF%), body fat mass (BFM)